2001
DOI: 10.1038/35086609
|View full text |Cite
|
Sign up to set email alerts
|

RPA governs endonuclease switching during processing of Okazaki fragments in eukaryotes

Abstract: Extensive work on the maturation of lagging strands during the replication of simian virus 40 DNA suggests that the initiator RNA primers of Okazaki fragments are removed by the combined action of two nucleases, RNase HI and Fen1, before the Okazaki fragments join. Despite the well established in vitro roles of these two enzymes, genetic analyses in yeast revealed that null mutants of RNase HI and/or Fen1 are not lethal, suggesting that an additional enzymatic activity may be required for the removal of RNA. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
513
4
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 321 publications
(544 citation statements)
references
References 29 publications
26
513
4
1
Order By: Relevance
“…WRN stimulation of EXO-1 5Ј-flap cleavage may serve a function during Okazaki fragment maturation or the processing of other DNA structures at the replication fork. Evidence presented here demonstrates that WRN is able to stimulate EXO-1 cleavage of flap structures with 5Ј-ssDNA tails up to at least 10 nt, an activity that may be important in a FEN-1 independent pathway of 5Ј-flap processing (53). Alternatively, EXO-1 may play a role in the removal of the terminal ribonucleotide at the RNA-DNA junction during Okazaki fragment processing in a WRN-stimulated reaction.…”
Section: Discussionmentioning
confidence: 95%
“…WRN stimulation of EXO-1 5Ј-flap cleavage may serve a function during Okazaki fragment maturation or the processing of other DNA structures at the replication fork. Evidence presented here demonstrates that WRN is able to stimulate EXO-1 cleavage of flap structures with 5Ј-ssDNA tails up to at least 10 nt, an activity that may be important in a FEN-1 independent pathway of 5Ј-flap processing (53). Alternatively, EXO-1 may play a role in the removal of the terminal ribonucleotide at the RNA-DNA junction during Okazaki fragment processing in a WRN-stimulated reaction.…”
Section: Discussionmentioning
confidence: 95%
“…It exhibits 5 0 -3 0 exonuclease activity and a structure-specific endonuclease activity by which DNA flap structures are cleaved (Harrington and Lieber, 1994). During DNA replication, Fen1 is responsible for the removal of Okazaki fragments (Bae et al, 2001). It also suppresses triplet repeat expansion generated by DNA slippage (Ruggiero and Topal, 2004) and facilitates the removal of mismatches that occur during synthesis of Okazaki fragments (Rumbaugh et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Reconstitution experiments have shown that although the majority of the displaced flaps are processed by the short flap pathway, a minority require the long flap pathway. Seo and colleagues originally proposed the Dna2 pathway as the primary means of Okazaki fragment processing (Bae et al 2001). Their proposal was likely influenced by genetic evidence in S. cerevisiae that Dna2 inactivation in cells was lethal, whereas FEN1 mutants only showed a slow-growing phenotype.…”
Section: Long Flap Pathwaymentioning
confidence: 99%
“…cerevisiae Dna2 can dissociate the RPA from a long flap (Bae et al 2001;Stewart et al 2008). Using a mechanism very similar to that of FEN1, Dna2 binds the flap base, and then threads the free 5 0 end of the flap ).…”
Section: Long Flap Pathwaymentioning
confidence: 99%
See 1 more Smart Citation